DAMPAK EKONOMI AKIBAT KEJAHATAN KORUPSI PASCA REGULASI OTONOMI DAERAH - Nur Rohim (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2014)
Abstract: Economic Impact Due to Corruption Crime After the existence of Regulatory Autonomy. Regional autonomy is regarded by the government as an antidote to regional political turmoil. It has been promised as an antidote to the highly centralized political and financial structures that never applied before. However, this expectation even leads to a shift of the corruption that was originally located in the center turning to the area. Therefore, it adversely affects economic improvement and welfare of the area. In example, there is emergence of new modes, either by manipulating the production and illegal cutting of the opinion. Keywords: Economic Impact, Corruptions, Regulatory Autonomy Abstrak: Dampak Ekonomi Akibat Kejahatan Korupsi Pasca Regulasi Otonomi Daerah. Otonomi daerah dianggap oleh pemerintah sebagai obat penawar gejolak politik daerah. Kebijakan ini dijanjikan sebagai suatu kutub berlawanan terhadap sistem politik dan struktur keuangan terpusat yang pernah diterapkan sebelumnya. Akan tetapi harapan ini malah berujung kepada pergeseran korupsi yang semula berada di pusat beralih ke daerah, sehingga berdampak ekonomi bagi peningkatan kesejahteraan rakyat daerah. Seperti munculnya modus-modus baru, baik dengan memanipulasi pengeluaran daerah maupun memotong secara ilegal pendapat daerah. Kata Kunci: Dampak Ekonomi, Korupsi, Otonomi DaerahDOI:10.15408/sjsbs.v1i1.1531